PENGARUH WORD OF MOUTH DAN CITA RASA TERHADAP KEPUTUSAN PEMBELIAN AYAM GEPREK JUARA (PADA MASYARAKAT MERR SURABAYA) - Wati, Lely Indah; Pujianto, Agung; Andayani, Sri (Research Journal of Social Science and Economics, 2025)
This study aims to examine the significance of the influence of Word of Mouth (WOM) and taste on purchasing decisions for champion geprek chicken. The approach used in this study is a quantitative method. The media used is a questionnaire as a research instrument. Technical analysis uses multiple linear regression with hypothesis testing, including the R test, t test, and F test. The number of samples in this study were 96 respondents who were selected using the Purposive Sampling method. The results showed that the Word of Mouth and taste variables had a positive and significant influence on the purchasing decision of champion geprek chicken. The influence of word of mouth and taste on purchasing decisions is 61%, while the remaining 39% is influenced by other factors not examined in this study.